Multifunctional graphene oxide-bacteriophage based porous three-dimensional micro-nanocomposites. Issue 28 (4th July 2019) - Passaretti, Paolo; Sun, Yiwei; Khan, Inam; Chan, Kieran; Sabo, Rania; White, Henry; Dafforn, Timothy R.; Oppenheimer, Pola Goldberg
Abstract : An alternative self-assembly strategy based on low-interactions for the fabrication of graphene-based sponges, using M13 bacteriophage as a cross-linking agent. Abstract : Graphene, since its successful exfoliation and characterisation has been continuously drawing extensive research interests due to its potential for a broad range of applications ranging from energy, microelectronics, through polymer fillers and sensors to environmental and biomedical devices. Exploitation of its unique chemical and physical properties for the manufacturing of functional materials, requires careful structural control and scaling-up into three-dimensional morphologies. Here, a facile method is established to create and control the bottom-up self-assembly of graphene oxide nano-sheets via unprecedented integration with a highly versatile bio-ingredient, the filamentous bacteriophage M13, into hierarchical, three-dimensional, porous sponges of GraPhage13 . This study explores the interplay of the GraPhage13 structure formation and studies the mechanisms that give rise to the controllable self-assembly. The straightforward fabrication of robust hierarchical micro-nano-architectures further lays a platform for applications in energy storage and conversion, catalysis and sensing.